- #1

- 130

- 0

I came up with A = -1/5 and B = 15.

Then, I had (1/15)*[(x-5)/(3x)] = Be^t. But this is where things break down. I thought B = -1/2. Yet the book's answer is 10/(2+3e^15t). What am I missing?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter cue928
- Start date

- #1

- 130

- 0

I came up with A = -1/5 and B = 15.

Then, I had (1/15)*[(x-5)/(3x)] = Be^t. But this is where things break down. I thought B = -1/2. Yet the book's answer is 10/(2+3e^15t). What am I missing?

- #2

Mark44

Mentor

- 34,987

- 6,739

I get A = -1/5 and B = +1/5.So I am being asked to use partial fractions to solve ODE's. In particular, I have (dx/dt) = 3x(x-5) with x(0) = 2.

I came up with A = -1/5 and B = 15.

When you separate the diff. eqn., it's a little more convenient to write it as

dx/(x(x - 5)) = 3dt

rather than having a denominator of 3x(x - 5) on the left side.

I also get x(t) = 10/(2 + 3e^(15t))

Then, I had (1/15)*[(x-5)/(3x)] = Be^t. But this is where things break down. I thought B = -1/2. Yet the book's answer is 10/(2+3e^15t). What am I missing?

- #3

- 130

- 0

(5-x)/x = Ce^15t.

When I solve that for x, I get x = 5/(1+Ce^15t). Yikes, where am I going wrong? I ran thru it twice and still don't see where I'm missing the 3 and 10?

- #4

Mark44

Mentor

- 34,987

- 6,739

You have switched a sign somewhere. I get (x - 5)/x = Ae^(15t), which is a little different from what you got. I also found that A = -3/2.Okay so I tried that and after using PF's and exponentiating, I get the following:

(5-x)/x = Ce^15t.

When I solve that for x, I get x = 5/(1+Ce^15t). Yikes, where am I going wrong? I ran thru it twice and still don't see where I'm missing the 3 and 10?

- #5

- 130

- 0

So I'm confused, is A=3/2 or the 1/5? I'm getting 1/5?

- #6

Mark44

Mentor

- 34,987

- 6,739

Sorry, I meant to write (x - 5)/x = Ce^(15t). C = - 3/2.

1/x + 1/(x - 5) = (-1/5)/x + (1/5)/(x - 5)

1/x + 1/(x - 5) = (-1/5)/x + (1/5)/(x - 5)

Share: